Serum-derived small extracellular vesicles as biomarkers for predicting pregnancy and delivery on assisted reproductive technology in patients with endometriosis - Muraoka, Ayako; Yokoi, Akira; Yoshida, Kosuke; Kitagawa, Masami; Bayasula,; Murakami, Mayuko; Miyake, Natsuki; Sonehara, Reina; Nakamura, Tomoko; Osuka, Satoko; Kajiyama, Hiroaki (Frontiers in Endocrinology, 2025)
IntroductionEndometriosis can cause of infertility, and evaluation methods for predicting clinical pregnancy outcomes are desired. Extracellular vesicles (EVs) exist in blood and it contains small non-coding RNAs (ncRNAs) that may reflect disease severity. In this study, we investigated small ncRNAs in serum EVs to identify specific biomarkers for predicting clinical pregnancy.MethodsSerum samples were collected from 48 patients who underwent assisted reproductive technology (ART). EVs were successfully isolated from serum samples and characterized using nanoparticle tracking assays, electron microscopy, and western blotting of EV’s markers. We performed small RNA sequencing and analyzed microRNA (miRNA) profiles in the infertility patients with and without endometriosis to detect pregnancy-predicting biomarkers.ResultsCandidate miRNAs in serum EVs were selected by comparing patients without endometriosis who became pregnant (n = 13) with those who did not (n = 21). A total of 241 miRNAs were detected; however, no trends separated the two groups. Next, EVs from patients with endometriosis were analyzed and divided into pregnant (n = 4) and non-pregnant (n = 10) cases. Among the 224 candidate miRNAs, miRNA profiles of pregnant women with endometriosis were separated from those of non-pregnant women by receiver-operating characteristics (ROC) curve analysis (area under the curve [AUC] > 0.8). In patients with endometriosis, serum EVs may be useful for predicting possible pregnancy before infertility treatment. Finally, we used small RNA sequencing of the tissue to demonstrate that pregnancy-predicting miRNAs in serum EVs were produced from endometriosis lesions. Although no predictors were found from miRNAs in serum EVs without endometriosis, miRNAs in serum EVs of patients with endometriosis could provide novel noninvasive biomarkers to predict pregnancy and have potential clinical applicability in ART.DiscussionFurther studies are required to examine the functional importance of these miRNAs to elucidate the pathological mechanisms of endometriosis and pregnancy.